An analysis of Turkey's regional agenda in Yemen's civil war (2014 - 2021) - Mahmoud, Maryam Jamal (My University, 2023)
Bu araştırma, bir bölgedeki iç savaşlara yönelik dış politikayı ve Ortadoğu'da bölgesel nüfuz aracı olarak bölgesel krizlere dahil oluşunu, Türkiye'nin Yemen iç savaşındaki rolü üzerinden analiz etmeyi amaçlamaktadır. Türkiye’nin Yemen iç savaşı sırasında, bölgesel pozisyonu için savaşın diğer aktörleriyle ilişkilerini de kapsayan veya Yemen’e yönelik dış politikaya dair kısıtlı sayıda araştırma bulunmaktadır. Bu nedenle, bu çalışma, Türkiye'nin Suudi Arabistan, BAE ve İran ile olan ilişkileri de dikkate alınarak, Yemen ve Körfez bölgesinde potansiyel bir rol üstlenmek için kullandığı dış politika stratejileri doğrultusunda Yemen iç savaşı’ndaki konumunu incelemektedir. Bu tezin temel amacı, Türkiye’nin Ortadoğu’ya yönelik dış politikasını Arap Baharı sonrası Yemen iç savaşı üzerinden incelemektir. Türkiye'nin müdahilliği, Orta Doğu'nun bölgesel güvenlik karmaşasındaki olayların seyri düşünüldüğünde önemli ve kritik bir faktördür. Bu tez, Türk dış politikasının geleceğini ve Türkiye'nin Ortadoğu'daki, özellikle de Yemen'deki rolünü analiz etmeye çalışmaktadır. Türkiye’nin savaşa dahil olma sürecini, saiklerini, stratejik çıkarlar ve insani amaçlarını ve yöntemlerini değerlendirmektedir. Araştırmacı, gerekli verileri toplamak için nitel araştırma yöntemlerini kullanmıştır.

This research seeks to analyze foreign policy towards civil wars within a region and the regional involvement as means of regional influence in the Middle East, through Turkey’s foreign policy and regional agenda in Yemen’s civil war. There is limited research available on Turkish foreign policy towards Yemen, especially during the current Yemeni civil war, with its regional interests attached with actors involved in the war. Nevertheless, in recent history, Yemen has struggled with a humanitarian crisis that has been caused by blockades of humanitarian aid and destruction of significant institutions such as hospitals and schools. Therefore, this study explores Turkey’s position in the war with reference to its regional agenda and the foreign policy strategies it is using to have a potential major role in Yemen, with considerations to its relations with Saudi Arabia, UAE, and Iran, who are state actors involved in the Yemeni civil war. The primary aim of this thesis is to examine Turkish foreign policy towards the Middle East in retrospect to the Yemeni civil war after the Arab Spring. Turkey’s involvement is a significant and decisive factor on the courses of events in the Middle East’s regional security complex. This paper attempts to anticipate Turkey’s role in the Middle East and the future of Turkish foreign policy, especially with its role in Yemen. It evaluates the involvement process in the war with consideration of its motives as strategic interests and humanitarian purposes. To collect the necessary data, qualitative research methods has been utilized.
Keywords: Bölgesel Güvenlik Kompleksi; Civil War; Civil war, 1994; Dış ilişkiler; Dış Müdahale Regional Security Complex; Foreign Intervention; Foreign relations; History; İç Savaş; İç Savaş, 1994; Politics and government; Siyaset ve yönetim; Tarih; Turkey; Türkiye; Yemen; Yemen (Cumhuriyet); Yemen (Republic)